Development Of Liveworksheet-Based Professional Ethics Lkpd To Increase Students’ Learning Engagement - Febriyanty, Anisa; Utomo, Supri Wahyudi; Sulistyowati, Nur Wahyuning (International Journal of Education, Vocational and Social Science, 2024)
The purposes of this study are to analyze: 1) the development stages of student worksheets (LKPD) using Liveworksheets to enhance student motivation in Professional Ethics, 2) the suitability of these Liveworksheets-based LKPD for teaching Professional Ethics to Grade X students, and 3) how these worksheets improve motivation among these students in Professional Ethics classes. The study follows the Borg and Gall development theory, going through the first six stages: 1) preliminary research; 2) data collecting; 3) products design; 4) design verification; 5) design modification; and 6) product testing. The participants of this research were Grade X students from SMKN 2 Madiun. The methods for data collection included observations, interviews, and questionnaires. The findings reveal that: 1) the development of LKPDs using Liveworksheets significantly impacts students due to the prevalent use of digital devices in education; 2) these LKPD, according to linguists, media experts, and subject matter experts, are deemed suitable for educational testing; and 3) Liveworksheets-based web LKPD successfully enhance students' learning motivation in Professional Ethics.